Briefly the Comprehensive Musicianship Concept for Shenyang Conservatory of Music, Liaoning Province - Yue, Sunye; หิรัญรักษ์ ศักดิ์ชัย (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
In this article, the author was commissioned by the Department of Piano to review documents related to the Comprehensive Musicianship for the development of documentation for teaching piano practice by searching for documents from academic databases in China and the West. In summary, a comprehensive music teaching concept developed from an experimental research project at the Institute of Wisconsin. Concept-based teaching principles that consider the development of musical creativity, musical performance, and critical listening and analysis are summarized as follows: Setting goals and planning good rehearsals that develop musical skills and understanding. Participation in a variety of status roles for example, arrangers, composers, music analysts, musicians, music performers and music listeners 3. Comprehensive music teaching, content integration, and increase opportunities for learners to gain experience in and outside of Western music. 4. Assessment of learning by teachers, learners, and viewers at every step of the experience.